PEMBUATAN VIDEO PROFIL UNTUK MENGOPTIMALISASI POTENSI WISATA DESA PESISIR - Saraswati, Ni Luh Gede Rai Ayu (Buletin Udayana Mengabdi; Vol 24 No 4 (2025): Buletin Udayana Mengabdi, 2024)
Perancak village is one of the coastal villages among the ten villages in Jembrana District, Bali. Perancak village is classified as advance village and categorized as pioneer village with its potential to develop its coastal tourism. There are several tourism attractions that is potentially to develop in the village, includes mangrove ecotourism, turtle conservation and Taman Ujung Perancak. As coastal village, Perancak village also has its featured product from fisheries sector called Bedetan. The lack of information on the tourism attraction in Perancak village website causing the village tourism is underdeveloped and unheard by the tourist. Profile video production can be a promotion tool to share the village natural resources and featured product effectively to improve the tourism visit to the village. However, the village profile video is not in the top priority by the village authority. This project aims to help the village in producing a cinematic village profile video through Udayana Community Service Program Chapter XXVII 2023. It is expected that the Perancak village profile video can provide a comphrehensive information, including the village history, tourism attractions and village featured product. Keywords: Perancak Village, Video Profile, KKN PPM Udayana, Coastal Ecotourism .